2019
DOI: 10.1523/eneuro.0124-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic Activation of Excitatory Neurons Alters Hippocampal Neurotransmission in a Dose-Dependent Manner

Abstract: Designer receptors exclusively activated by designer drugs (DREADD)-based chemogenetic tools are extensively used to manipulate neuronal activity in a cell type-specific manner. Whole-cell patch-clamp recordings indicate membrane depolarization, coupled with increased neuronal firing rate, following administration of the DREADD ligand, clozapine-N-oxide (CNO) to activate the Gq-coupled DREADD, hM3Dq. Although hM3Dq has been used to enhance neuronal firing in order to manipulate diverse behaviors, often within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Given that thus far very few studies have used chemogenetic strategies during developmental time windows ( Teissier et al, 2020 ; Wong et al, 2018 ), we characterized the consequences of hM3Dq DREADD activation of forebrain excitatory neurons in the postnatal window using both electrophysiological and biochemical approaches. Our observation of hM3Dq DREADD-mediated induction of robust spiking activity in postnatal slices parallels observations made in adulthood ( Alexander et al, 2009 ; Pati et al, 2019 ). Chronic chemogenetic hM3Dq DREADD activation during postnatal life enhanced neuronal activity marker expression in the hippocampus and cortex, as well as increased network activity, enhanced spontaneous excitatory events, and reduced spontaneous inhibitory events in CA1 pyramidal neurons in PNCNO-treated mouse pups.…”
Section: Discussionsupporting
confidence: 89%
“…Given that thus far very few studies have used chemogenetic strategies during developmental time windows ( Teissier et al, 2020 ; Wong et al, 2018 ), we characterized the consequences of hM3Dq DREADD activation of forebrain excitatory neurons in the postnatal window using both electrophysiological and biochemical approaches. Our observation of hM3Dq DREADD-mediated induction of robust spiking activity in postnatal slices parallels observations made in adulthood ( Alexander et al, 2009 ; Pati et al, 2019 ). Chronic chemogenetic hM3Dq DREADD activation during postnatal life enhanced neuronal activity marker expression in the hippocampus and cortex, as well as increased network activity, enhanced spontaneous excitatory events, and reduced spontaneous inhibitory events in CA1 pyramidal neurons in PNCNO-treated mouse pups.…”
Section: Discussionsupporting
confidence: 89%
“…When we pan-neuronally expressed hM3D-G(q) DREADDs, which will increase excitability and intracellular calcium levels (Alexander et al, 2009;Pati et al, 2019), activation of the DREADDs with CNO injections caused increases in gamma-band power relative to vehicle (Fig. 2F,basal 18.6±11.2%,p<0.02;locomotion,43.6±15.0%, ).…”
Section: Bi-directional Chemogenetic Manipulation Of Local Neural Actmentioning
confidence: 97%
“…In addition, it has been reported that 20 μmol/L CNO results in faster increase in intracellular calcium levels compared to 1 μmol/L CNO in primary hippocampal neurons and that CNO at more than 20 μmol/L would not result in more enhanced neuronal activity …”
Section: Resultsmentioning
confidence: 99%